Analysis of Blasting Failure Characteristics and Damage Mechanism of Different Rock Mass Elastic Modulus Under Deep Crustal Stress. Issue 1 (February 2021) - Wang, Bo; Xie, Liangfu; Zhu, Qingyang; Cui, Jianbin
Abstract: In order to study the effect of elastic modulus of rock mass under deep crustal stress on blasting failure characteristics and damage mechanism, this paper simulates rock blasting with different elastic modulus through particle flow software. The blasting failure characteristics of rock mass are obtained by reading the peak stress changes from the measuring points. The damage mechanism of rock blasting is revealed from the aspects of crack distribution, crack development trend, fragment formation. The results show that: As the elastic modulus increases, the peak stress of each measuring point is gradually decreasing; with the increase of elastic modulus, the macro cracks of rock mass become shorter after blasting; when the elastic modulus is 48 GPA, the number of cracks is the largest and the development is relatively gentle.